2015
DOI: 10.3390/ijgi4041982
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Analysis of Regional Inequality based on Spatial Field Model: A Case Study of China from 2000 to 2012

Abstract: A large body of recent studies-from both inside and outside of China-are devoted to the understanding of China's regional inequality. The current study introduces "the spatial field model" to achieve comprehensive evaluation and multi-scale analysis of regional inequality. The model is based on the growth pole theory, regional interaction theory, and energy space theory. The spatial field is an abstract concept that defines the potential energy difference that is formed in the process of a regional growth pole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Over the past decade, central and provincial governments have sought to foster urban agglomerations as regional growth poles and as strategic core areas with the potential to drive continuous economic growth [77]. In this context, the study of urbanization in the MYRB is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, central and provincial governments have sought to foster urban agglomerations as regional growth poles and as strategic core areas with the potential to drive continuous economic growth [77]. In this context, the study of urbanization in the MYRB is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The change of the long axis is more obvious than that of the short one, meaning that the forces driving the spatial evolution mainly come from urban expansion in the "northwest-southeast" direction. Specifically, in 2000-2008, the short axis varied more than the long axis, that is, the "southwest-northeast" direction had rapid urban expansion during 2000-2008. In 2008, the long axis varied more than the short axis, indicating that the "northwest-southeast" had rapid urbanization during 2008-2016.…”
Section: Evolution Of the Spatial Structure In The Myrb Urban Agglomementioning
confidence: 99%
“…We express this with the example of spatial autocorrelation (hot spot analysis), which helps to reveal spatial patterns. Yet, for better data comparability across different systems (such as countries) or across time at different geographical levels [6], it would be best to work with a regular grid. To do this, we first have to recalculate the values from source units to this regular grid.…”
Section: Introductionmentioning
confidence: 99%
“…The GDP per capita of Tianjin, the wealthiest province, was nearly 4.1 times more than that of the poorest province. Regional inequality in China is much higher than in some developed countries [4]. For instance, in 2015, Alaska's GDP per capita (73,474 dollars) was the highest in America, while the lowest was in Mississippi, where it was 35,717 dollars.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, numerous studies have indicated that the NTL satellite imagery has been shown to be highly related to socioeconomic parameters [15][16][17][18][19][20]. Due to its evident advantages, associated with easy access, low cost, and relative objectivity, some social economists use night light data to study regional inequality [4,[21][22][23][24][25]. For instance, Lessmann and Seidel [21] provided a new dataset of regional income inequalities within countries, based on DMSP-OLS satellite NTL data.…”
Section: Introductionmentioning
confidence: 99%